Ten misconceptions about current account imbalances in the euro area - Jürgen Matthes (Intereconomics, 2014)
In the pre-crisis period, substantial current account imbalances built up in the euro area. Despite recent progress in economic rebalancing, especially in the countries mostly affected by the euro debt crisis, a controversial debate is still raging about past causes, current interpretations and future outlooks for the current account positions of euro area countries. This article examines ten common claims often heard in the public debate and critically discusses their economic foundation.
Keywords: 330